Representasi Makna Harmonisasi Keluarga pada Iklan Ikea - Marsha Salsabila; Wiki Angga Wiksana (UNISBA Press, 2023)
Abstract. Advertisements also have the characteristics of being attractive to the masses if they provide clear, concise, and concise information on the broadcast. Promotional content also contains compelling messages to help viewers choose the product they are looking for. For example, there is an IKEA ad. The IKEA advertisement describes the interior exhibited by the family in terms of the use of the interior which is the object of promotion. The object of this research is a snippet of a scene in an IKEA advertisement that relates to the focus of the research problem. The aim of the researcher in this study is to find out the meaning of denotation, connotation, and myth in the IKEA Indonesia advertisement in 2021. The research method used in this study uses a qualitative method. From the results of this study, it was found that the representation of family harmonization in the IKEA 2021 advertisement was in accordance with the semiotic analysis of the Roland Barthes model, namely trying to meet family needs, helping families to meet the needs of living together, helping individual family members at home, providing information to trusted people in the family environment, decorating tools for families, working to meet family needs, and gathering together with cheerful feelings. Abstrak. Iklan juga memiliki sifat yang menarik untuk ditonton massa jika iklan yang ditayangkan memberi informasi yang sifatnya jelas, singkat, dan padat pada siaran. Konten promosi juga berisi pesan yang menarik untuk membantu pemirsa memilih produk yang mereka cari. Misalnya ada pada iklan IKEA. Iklan IKEA menggambarkan interior yang diperagakan oleh keluarga dari segi kegunaan interior yang menjadi objek promosi. Objek penelitian ini adalah potongan gambar dalam adegan yang terdapat di iklan IKEA yang berkaitan dengan fokus masalah dari penelitian. Tujuan yang dimiliki oleh peneliti dalam penelitian ini yaitu untuk mengetahui makna denotasi, konotasi, dan mitos pada iklan IKEA Indonesia tahun 2021. Metode penelitian yang dilakukan dalam penelitian menggunakan metode kualitatif. Dari hasil penelitian ini ditemukan bahwa representasi harmonisasi keluarga dalam iklan IKEA 2021 sesuai dengan analisis semiotik model Roland Barthes yaitu berusaha memenuhi kebutuhan keluarga, membantu keluarga untuk memenuhi kebutuhan hidup bersama, membantu individu anggota keluarga dirumah, memberikan informasi kepada orang yang dipercaya di lingkungan keluarga, mendekorasi alat untuk keluarga, bekerja untuk memenuhi kebutuhan keluarga, dan berkumpul bersama dengan perasaan ceria.